Down Wadding Thermal Insulation Performance in Different Placement Conditions (Journal of Fiber Bioengineering and Informatics, 2025)
Warmth is a key consideration for consumers when choosing products. Existing research has mostlyfocused on testing the warmth performance of down products in a horizontal state, neglecting the non-horizontal state during actual wearing. This study investigates the thermal insulation performanceof down waddings under different placement conditions and their interrelationships. Four types ofstitching spacing and five types of unit filling amounts are determined through market research, and20 pieces of down waddings are made. Thermal resistance experiments are conducted in both horizontalplacement and 24-hour suspension states. The experimental results show that under 24-hour suspension,the thermal resistance value of down waddings generally decreases; Under the same stitching spacingconditions, the unit filling amount corresponding to the maximum thermal resistance value in the 24-hour suspension state has decreased; There is a significant difference in thermal resistance values betweenthe two placement states, with a Pearson correlation coefficient of 0.939, indicating a strong positivecorrelation; A mathematical regression model $y=0.825x + 0.033$ is established through SPSS analysisto describe the relationship between the thermal insulation of down wadding in two different placementconditions. The findings of this study provide an important theoretical basis and practical guidance forfurther research, design, and production of down products.